The Influence of Knowledge Sharing and Self-Efficacy on Innovative Behavior in Sales Employees in Cirebon - Afrizal Fathur Rachman; Moch Rakan Siraj (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of knowledge sharing and self-efficacy on innovative behavior within a sales employee environment. It employs quantitative methods to collect primary data through the distribution of Likert scale questionnaires directly to sales companies in Cirebon City. Secondary data were gathered from research methodology books as well as national and international academic journals. The researchers used SPSS for data analysis to test the hypotheses and research models. Using a non-probability purposive sampling method, the study sampled 163 sales employees from various companies. Knowledge sharing, which reflects the willingness and ability of individuals to exchange information with colleagues, and self-efficacy, which refers to an individual's belief in their capability to complete tasks and face challenges, are identified as key factors in driving innovation. Through a quantitative approach using a survey method, data were collected from respondents across various industry sectors. The analysis indicates that knowledge sharing significantly enhances individuals' propensity to innovate, while self-efficacy positively and significantly influences innovative behavior. The implications of this study highlight the importance of fostering a culture of knowledge sharing and strengthening self-efficacy within organizations to create a dynamic and innovative work environment.